Microplastics as an Emerging Environmental Pollutant in Agricultural Soils: Effects on Ecosystems and Human Health - Yu, Hong; Zhang, Ying; Tan, Wenbing; Zhang, Zheng (Frontiers in Environmental Science, 2022)
Microplastics are < 5 mm in size, made up of diverse chemical components, and come from multiple sources. Due to extensive use and unreasonable disposal of plastics, microplastics have become a global environmental issue and have aroused widespread concern about their potential ecological risks. This review introduces the sources, distribution and migration of microplastics in agricultural soil ecosystems. The effects of microplastics on soil physicochemical properties and nutrient cycling are also discussed. Microplastics can alter a series of key soil biogeochemical processes by changing their characteristics, resulting in multiple effects on the activities and functions of soil microorganisms. The effects of microplastics on soil animals and plants, the combined effects of microplastics and coexisting pollutants (organic pollutants and heavy metals), and their potential risks to human health are also discussed. Finally, prevention and control strategies of microplastic pollution in agricultural soil ecosystems are put forward, and knowledge gaps and future research suggestions about microplastic pollution are given. This review improves the understanding of environmental behavior of microplastics in agricultural soil ecosystems, and provides a theoretical reference for a better assessment of the ecological and environmental risks of microplastics.